The challenges of livelihoods reconstruction in the context of informal settlement upgrading. (February 2021) - Cherunya, Pauline C; Truffer, Bernhard; Samuel, Edinah Moraa; Lüthi, Christoph
Community involvement is recognized as a core condition for success in informal settlements upgrading. However, the wider ramifications of this requirement are not well understood. Mostly, community involvement has been equated with a narrow interpretation of participation, largely focusing on the elicitation of dwellers' preferences at the planning stages. We argue that this approach overlooks the actual needs for livelihoods reconstruction in the course of upgrading. To better conceptualize these requirements, we propose to analyse the time–space configuration of practices, which we frame as constituting Oscillating Domestic Spaces . The concept illustrates the contingent nature of daily activities to meet livelihoods needs and how people navigate these conditions. Challenges associated with reconstructing new domestic spaces are illustrated using the Kenyan Slum Upgrading (Kensup) initiative in Nairobi, Kenya. The findings suggest that an inadequate understanding and consideration of livelihoods reconstruction reduced legitimacy of the initiative, resulted in rapid deterioration of physical amenities and relegated most of the alleged 'beneficiaries' deeper into poverty. We suggest that, for successful settlements upgrading, livelihoods reconstruction should be a core process in the planning, implementation and post-implementation stages.